Sinergitas Efek Kombinasi Ekstrak Daun SirsaK (Annona muricata Linn) Dengan Doksorubisin Pada Sel Kanker Payudara MCF-7 - Lukman; Aswad, Hijral; Lestari, Desy Ayu; Paluseri, Andi (Media Farmasi, 2024)
Doxorubicin is the first line of cancer treatment but has very serious side effects such as hair loss, kidney damage and liver function abnormalities. One strategy to reduce these side effects is to combine doxorubicin with medicinal plants with anti-cancer properties such as soursop leaves (Annona muricata Linn). The aim of this research is to determine the synergistic effect of the combination of soursop leaf extract with doxorubicin to inhibit the growth of MCF-5 breast cancer cells. Soursop leaves were extracted with 96% ethanol while the anti-cancer test used the MTT method. The results of the study showed that soursop leaf extract had anti-cancer properties with IC25 and IC50 respectively being 29.36 ± 1.16 and 58.75 ± 2.35 µg/mL while doxorubicin was 1.34 ± 0.04 and 2. 76 ± 0.03 µg/mL. The combination of soursop leaf extract and doxorubicin showed a value of 0.8-1.0 (moderate synergistic). In conclusion, the combination of soursop leaf extract and doxorubicin shows a synergistic effect.